A real-time Global Warming Index. Issue 1 (December 2017) - Haustein, K.; Allen, M.; Forster, P.; Otto, F.; Mitchell, D.; Matthews, H.; Frame, D.
Abstract We propose a simple real-time index of global human-induced warming and assess its robustness to uncertainties in climate forcing and short-term climate fluctuations. This index provides improved scientific context for temperature stabilisation targets and has the potential to decrease the volatility of climate policy. We quantify uncertainties arising from temperature observations, climate radiative forcings, internal variability and the model response. Our index and the associated rate of human-induced warming is compatible with a range of other more sophisticated methods to estimate the human contribution to observed global temperature change.